2021
DOI: 10.3390/v13040591
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Jumbo Phage from Leaf Litter Compost and Its Suppressive Effect on Rice Seedling Rot Diseases

Abstract: Jumbo phages have DNA genomes larger than 200 kbp in large virions composed of an icosahedral head, tail, and other adsorption structures, and they are known to be abundant biological substances in nature. In this study, phages in leaf litter compost were screened for their potential to suppress rice seedling rot disease caused by the bacterium Burkholderia glumae, and a novel phage was identified in a filtrate-enriched suspension of leaf litter compost. The phage particles consisted of a rigid tailed icosahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Among them, six jumbo Ralstonia phages: RSL1, RSF1, RSL2, RP12, RP31, and RsoM2USA, having genomic DNA >200 kbp are considered to have a broad host range [4][5][6][7][8]. Furthermore, it has been reported that three jumbo Burkholderia phages: FLC6, FLC8, and FLC9, isolated from leaf litter compost have the ability to lyse multiple isolates of R. pseudosolanacearum [9][10][11]. To establish practical jumbo phage-based biocontrol agents with lytic potential against a broad range of pathogenic Ralstonia spp.…”
Section: Full Textmentioning
confidence: 99%
“…Among them, six jumbo Ralstonia phages: RSL1, RSF1, RSL2, RP12, RP31, and RsoM2USA, having genomic DNA >200 kbp are considered to have a broad host range [4][5][6][7][8]. Furthermore, it has been reported that three jumbo Burkholderia phages: FLC6, FLC8, and FLC9, isolated from leaf litter compost have the ability to lyse multiple isolates of R. pseudosolanacearum [9][10][11]. To establish practical jumbo phage-based biocontrol agents with lytic potential against a broad range of pathogenic Ralstonia spp.…”
Section: Full Textmentioning
confidence: 99%
“…The application of bacteriophages is not limited to medical use in animals and humans. In agriculture, they are used to treat different problems with bacterial contamination [ 68 , 69 , 70 ]. In the food industry, they are used as a microbiological control method for undesirable pathogens, increasing food safety [ 71 , 72 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…For BPB disease management, various bacterial genera, including Bacillus [11], Burkholderia [54], Pantoea [10], Pseudomonas [57], and Streptomyces [58,61] have been applied to the rice seeds. Instead of bacteria, bacteriophages also have used seed application to manage BPB disease [71,75]. However, the primary constraint of seed application is that seeds can only be integrated with a limited amount of BCA, which can be a limiting issue because a successful biological control activity might require a specific amount of BCA.…”
Section: Utilization Of Bca For Bpb Disease Management: Constraints A...mentioning
confidence: 99%
“…With rice, bacteriophages have been applied as BCA to control BPB pathogens under in vitro and glasshouse conditions. Under in vitro conditions, bacteriophages from leaf, namely FLC5 [70] and FLC6 [71] were examined genomically and showed potential application as BCAs to control B. glumae . In another related study, bacteriophages from rice seed extract, including bacteriophage Ф813, Ф843, and Ф173 showed antagonistic activity against B. glumae [74].…”
Section: Management Of Bpb Disease Using Bcamentioning
confidence: 99%